Edukasi Pencegahan Penyebaran Covid-19 Pada Masyarakat Desa Panggulawu Kabupaten Konawe Utara Di Era New Normal - Ismail, Darwin; Kadir, Laode A.; Wahab, Wahab (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2021)
Panggulawu village lies along Panggulawu beach of Sawa, northern konawe district, Southeast Sulawesi province. This village is mainly occupied by civil servants (PNS), fishermen and farmers. Nowadays, It is every citizen’s responsibility to remind each other about the danger of Covid-19 and the importance of how to limit the spread of the disease. Considering this issue, Institute of Research and Community Service Halu Oleo University arranged a team consisting of 3 academic-staff; two of them from Chemistry study program and one from Mining study program, and 3 students. All the three students were from Chemistry Department.  The aims of the team sent to the village is to educate people of Panggulawu about how to minimize the spread of Covid-19 disease. The method used in this community service included is public talking (mini seminar). During this community service, villagers got involved actively in discussion and participating actively during demonstration. They and their leaders were equally very enthusiastic and supportive.